Mass Communication Tools Influence on Legal Consciousness in Modern Individuals: Key Features - Bazayev, Oleksii (Problems of legality, 2025)
The article is devoted to a comprehensive analysis of the features of the influence of mass media on the legal consciousness of modern man. The relevance of the study is due to the acceleration and scaling of the influence of mass media on the formation of public and individual legal consciousness in the conditions of the information society. Mass communication tools are increasingly acting as leading agents of the socialization of the individual and his involvement in the legal discourse. It is the daily connection of a person with mass media that creates the need for a systematic study of theories and mechanisms of their functioning. The purpose of the study is a comprehensive philosophical and legal analysis of the features of the influence of mass media on the legal consciousness of modern man and the determination of key patterns and consequences of this process. To achieve this goal, a set of methods of scientific knowledge was applied: interdisciplinary, systemic, comparative and structural-functional. As a result of the study, the distinction between the concepts of «mass media» and «mass communication tools» in modern scientific discourse was established, which reflects the transition to dialogical and interactive communication in the information society. Key theories and concepts that reveal the mechanisms of influence of mass media on the legal consciousness of modern man were considered. The ambivalent nature of the influence of mass media was recognized, which can both contribute to the formation of legal culture and critical thinking, and be a tool for manipulation, dehumanization, the basis for the formation of deviant behavior and other manifestations of a deformed legal consciousness. The vectors of the influence of mass media on the process of forming a person’s legal consciousness were determined. The conclusions indicate that the influence of mass media is multi-vector in nature and occurs at different levels - psychological, cognitive, emotional-value, socio-political and cultural. Mass media increasingly determine the contours of the legal culture of society, and therefore, the formation of effective strategies to combat manipulative practices and the development of the ethical, legal and information culture of the population should become a key condition for maintaining the constructive influence of the media and strengthening the legal consciousness of modern people.